(Re) Percussões de “Missa dos Quilombos” (Orfeu, 2018)
This article proposes considerations on Missa dos Quilombos [Maroon’s Mass], an LP produced and recorded live in 1982, with music and arrangements by Milton Nascimento and lyrics by the priest Pedro Casaldáliga and Pedro Tierra, reedited on CD in 1995. We will take the phonograms as the main source of our analysis, but seeking to articulate them to the event and repercussions of the religious rite that generated the recording, insofar as these also contribute to elucidate the larger aesthetic and political project that encompasses all these records. Combining the interdisciplinary analysis of popular music studies with the historiographic investigation of printed sources, we hope, finally, to understand the Mass and its recording as participants in the Brazilian cultural history relevant for the democratic resumption precisely because of the way in which converge to them the main lines of the affirmation of cultural and religious afrodiasporic matrices as indispensable elements of Brazilian and Latin American history and society.
Keywords: African Diaspora; Cultural Hybridization; Popular Music; Maroon’s Mass